The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/2017sw001695
|View full text |Cite
|
Sign up to set email alerts
|

SWMF Global Magnetosphere Simulations of January 2005: Geomagnetic Indices and Cross‐Polar Cap Potential

Abstract: We simulated the entire month of January 2005 using the Space Weather Modeling Framework (SWMF) with observed solar wind data as input. We conducted this simulation with and without an inner magnetosphere model and tested two different grid resolutions. We evaluated the model's accuracy in predicting Kp, SYM‐H, AL, and cross‐polar cap potential (CPCP). We find that the model does an excellent job of predicting the SYM‐H index, with a root‐mean‐square error (RMSE) of 17–18 nT. Kp is predicted well during storm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 97 publications
5
79
0
2
Order By: Relevance
“…These metrics are summarized in Table . We note that the reported accuracy of this SYM‐H prediction is comparable to the operational configuration of the SWMF reported for this same month by Haiducek et al () and that the RAM predictions are less biased.…”
Section: Application Of the Standardized Assessment Setsupporting
confidence: 83%
See 2 more Smart Citations
“…These metrics are summarized in Table . We note that the reported accuracy of this SYM‐H prediction is comparable to the operational configuration of the SWMF reported for this same month by Haiducek et al () and that the RAM predictions are less biased.…”
Section: Application Of the Standardized Assessment Setsupporting
confidence: 83%
“…The 8‐differential‐equation model of Horton and Doxas () produces an output that can be considered a synthetic AL value. Gleisner and Lundstedt () adopted their neural network model for AE prediction, Bala et al () used their neural net for AE forecasts, Amariutei and Ganushkina () used the ARMAX model for predicting AL, Zhang and Moldwin () included AE in their probabilistic forecast of geomagnetic activity, and Haiducek et al () computed AL from the SWMF model results.…”
Section: Prior Assessment Of Index Prediction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the results obtained with the three simulations, we are able to assess qualitatively how sensitive the model‐derived K values are to the model settings. The three simulations are the same as those in Haiducek et al (), and details on the settings can be found there and in Haiducek et al (), which shares some of the settings in common. We describe them briefly here: SWMFa : Same settings as Ilie et al (), but with modifications to improve stability (details in Haiducek et al, ).…”
Section: Methodsologymentioning
confidence: 99%
“…A 0.25 R E cell size in the expected region of IB formation. Settings described in detail in Haiducek et al () where this model configuration is referred to as the “Hi‐res” configuration. SWMFc : A 1 million cell grid with settings based on those used operationally by the NOAA Space Weather Prediction Center. A 0.5 R E cell size in the expected region of IB formation.…”
Section: Methodsologymentioning
confidence: 99%